Circulating Immune Complexes Pre and Post Clotting Factor Infusion in Hemophilia - Gomperts, Edward D; Jordan, Stanley; Berg, Debbie; Sakai, Rebecca; Boylen, Lois (Thrombosis and Haemostasis, 1981)
Circulating immune complexes (CICs) were studied by the Raji cell radioimmune-assay (Raji-RIA) and Clq-solid phase assay (Clq-SPA) in sera samples obtained pre and post replacement infusion from 21 young hemophiliac patients (Mean age 9.5 years). Seven patients had repeat studies. Sixteen patients were selected randomly; the other five were selected as having potential infusion related disease processes. All patients had received multiple infusions prior to entering the study. Five patients were infused with FIX concentrates (2 Hemophilia B, one FVII deficiency, 2 with inhibitors to FVIII). Of the hemophilia A patients (13 severe; 3 mild/moderate), six were infused with ABO-Rh type specific cryoprecipitate and 10 were infused with factor concentrate. Preinfusion sera samples evaluated by the Raji-RIA showed 14 of 28 (50%) sera positive. Eleven of 28 (39.3 %) were positive post infusion in the Raji-RIA. Pre and post infusion studies of the same sera samples using the Clq-SPA showed 5 of 28 (17.9%) positive pre-infusion and 4 of 28(14.3%) positive post infusion. No statistically significant relationship between pre and post infusion studies could be demonstrated.There was no obvious correlation between CIC levels and patient age, race, Epe of infusate, ABO-Rh blood type, hepatosplenomegaly, the presence or absence of HBsAG, antibody, or chronic joint changes. CICs were detected in the three patients with SGOT/SGPT levels greater than 5 times normal, in both patients with chronic renal disease (chronic glomerulonephritis), and two children who had previously demonstrated a Coombs’-positive hemolytic anemia after factor concentrate infusion. Six of eight patients with extremely high levels of CICs had associated clinical or laboratory abnormalities.This data indicated that CICs (as detected by the Raji-RIA) are present in increased frequency in hemophiliac patients. Although individual patients developed CICs post infusion, there is no clinical or statistical data supporting a common infusate immunogen. CICs were present in patients with serum hepatitis and other immune related disorders, probably secondary to factor infusion. The immunopathogenicity and origin of CICs in hemophiliacs is uncertain.
Keywords: Circulating immune complexes hemophilia